ANALISIS PROSES REKRUTMEN, SELEKSI KARYAWAN, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. ANHONG MEDIA INTERNATIONAL - Christon; Christon, Christon; Saputra, Asron (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This study aims to investigate the influence of the recruitment process, employee selection, and work discipline on employee performance at PT. Anhong Media International in Kota Batam. Employing a quantitative approach, the research utilized a saturated sampling technique, involving the entire population of 107 individuals working at PT. Anhong Media International, located at Kompleks Pertokoan Gading Mas, Sungai Panas Kota Batam, Kepulauan Riau. Data collection was conducted through an online questionnaire employing a Likert scale. The collected data underwent comprehensive analysis using SPSS 26, encompassing descriptive statistical tests, data quality assessments, classical assumption tests, influence tests, and hypothesis testing. The multiple linear regression results revealed that the recruitment process (X1) holds a significant 25.8% impact on employee performance (Y1), employee selection (X2) influences employee performance (Y1) by 17.9%, and work discipline (X3) contributes to employee performance (Y1) by 25.5%. The combined effect of the recruitment process, employee selection, and work discipline on employee performance at PT. Anhong Media International is determined to be 25.8%, as indicated by the coefficient of determination (R2).